A revision of the Paracanthocobitis zonalternans (Cypriniformes: Nemacheilidae) species complex with descriptions of three new species - Singer, Randal A.; Pfeiffer, John M.; Page, Lawrence M. (Zootaxa, 2017)
The Paracanthocobitis zonalternans species complex is revised based on analysis of morphological and molecular data. Three new species, P. nigrolineata, P. marmorata, and P. triangula are described, and P. phuketensis is removed from synonymy. All species are described morphologically, geographic ranges are delimited, and relationships are discussed for those for which molecular data (cytochrome c oxidase subunit 1 - COI) are available. In view of the morphological similarities of some of the species, a surprising result of this study was the moderately large genetic distances among species. Uncorrected COI p-distances between geographic clades of P. zonalternans ranged from 7.6–9.3%, suggesting that the species are reproductively isolated from one another even though morphological changes are minor. Paracanthocobitis phuketensis, distributed in several rivers draining to the Gulf of Thailand and to the Andaman Sea, shows considerable intraspecific variation that should be explored in detail for historical and ecological explanations. Cobitis chlorosoma McClelland, 1839 from Assam, India, is a synonym of P. botia, not P. zonalternans.